Augmented reality marketing and consumer‒brand relationships: How closeness drives brand love - Philipp A. Rauschnabel; Verena Hüttl-Maack; Aaron C. Ahuvia; Katrin E. Schein (Psychology & Marketing, 2024)
Marketers use augmented reality (AR) to place virtual brand-related information into a consumer's physical context. Grounded in the literature on AR, brand love, metaphor theory, and closeness as interpreted by the neural theory of language, the authors theorize that branded AR content can reduce the perceived physical, spatial distance between a consumer and a brand. This perceived closeness subsequently drives the closeness of the emotional relationship in the form of brand love. Two empirical studies validate this framework. Study 1 shows that using an AR app (vs. non-AR) increases the perceived physical closeness of the brand, which in turn drives brand love (i.e., relationship closeness). Study 2 replicates this finding in a pre-/post-use design. Here, high levels of local presence (i.e., the extent to which consumers perceive a brand as actually being present in their physical environment) drive perceived physical closeness, which leads to brand love. We also find that AR's power to generate brand love increases when the consumer is already familiar with the brand. We discuss managerial implications for AR marketing today and in a metaverse future in which AR content might be prevalent in consumers' everyday perceptions of the real world.
Keywords: 650; augmented reality; brand love; closeness; consumer‒brand relationships; metaphor; metaverse; spatial computing; spatial distance